PENGARUH TAX TO BOOK RATIO DAN DEFERRED TAX TERHADAP KINERJA KEUANGAN (Studi Kasus pada Perusahaan yang Memanfaatkan Super Tax Deduction untuk Tahun 2021-2025) - Cindy Aliya Sekar Kharisma; Endang Kiswara (Diponegoro Journal of Accounting, 2026)
This study aims to analyze the effect of Tax to Book Ratio (TBR) and Deferred Tax (DT) on the financial performance of companies utilizing the Super Tax Deduction incentive. Financial performance is measured using Return on Assets (ROA), Return on Equity (ROE), and Net Profit Margin (NPM). The study employs secondary data obtained from the financial statements of companies utilizing the Super Tax Deduction incentive during the period of 2021–2025. The sample was selected using a multi-case study sampling method based on predetermined criteria. Data were analyzed using panel data regression with the assistance of EViews 13 software. The results indicate that Tax to Book Ratio has a negative and significant effect on ROA, ROE, and NPM. These findings suggest that a higher Tax to Book Ratio, which reflects a greater proportion of taxable income relative to accounting income, is associated with lower financial performance. Meanwhile, Deferred Tax does not have a significant effect on ROA, ROE, or NPM. This result indicates that changes in Deferred Tax expense or benefit are not sufficient to significantly influence corporate financial performance. Overall, the study demonstrates that Tax to Book Ratio plays a more dominant role than Deferred Tax in explaining the financial performance of companies utilizing the Super Tax Deduction incentive.